PERAN PENDIDIKAN AGAMA DI KELUARGA DALAM MENGURANGI PENYALAHGUNAAN NARKOBA DI KALANGAN REMAJA - Fauzi Caniago (Jurnal Sosio dan Humaniora (SOMA), 2022)
Generally, young people want to show their behavior and attitude trying to present and signalize their identity, so that very sensitive to changes that happened around, which mentioned can generate conflict in young people which affect negativity to growth of forming young people which is have opportunity to generate behavior which digressing ( delinquent ).One of the present day young people’s behavior able to be categorized into behavior digress from religion teaching is abuse of forbidden drug which more knowledgeable with term of Drug/Narkoba. Problem appear of this Drugs/Narkoba, have come to big problem more and more day, increase its amount and difficult to be controlled or discontinued. Abuse of Drugs/Narkoba among young people happened because less of construction of education specially education of religion and is diffuse of observation by their parents, so that they unable to control their passion .Therefore, to handle them should do steps by parents, such as 1). Give religion teaching at home 2). Fill the children free time.,3). Parent’s byword. 4). Parent’s attention ,5). Control to the children’s behavior ,6). Creating feel climate in the family 7). Teach child to save money 8). Help their talent and enthusiasm through art/cultural